Comparative Study on the Protection of the Right to Health through the Regulation of Cannabis Use in Indonesia and Thailand - Firdaus Mario Nathanael; Ratih Damayanti (Universitas Negeri Semarang, 2026)
Cannabis is a plant that has medicinal benefits. However, the use of cannabis is prohibited by Indonesian Law Number 35 of 2009 concerning Narcotics, which states that cannabis is a Class I narcotic and cannot be used for medical purposes. This is contrary to the right to obtain health services and the state is obliged to provide them. A number of studies on the medicinal benefits of cannabis plants have created a new debate in Indonesia regarding the relative benefits of constitutional regulation and medical treatment. In other state policies, Thailand has updated its cannabis legalization arrangements, which have had a good impact on several sectors. This paper aims to analyze the regulation of cannabis in Indonesia and in Thailand comparatively, as well as examine the impact of the regulation of cannabis legalization in Indonesia and in Thailand.